Nit‐Occlud Lê VSD coil versus Duct Occluders for percutaneous perimembranous ventricular septal defect closure. (17th July 2018) - Nguyen, Hieu Lan; Phan, Quang Tan; Dinh, Linh Huynh; Tran, Hieu Ba; Won, Hoyoun; Thottian, Julian Johny; Duc, Dung Doan; Quang, Truong Nguyen; Kim, Sang Wook
Abstract: Objective: To evaluate the efficacy and safety of Nit‐Occlud Lê VSD Coil versus Duct Occluders for percutaneous closure of perimembranous ventricular septal defect (pmVSD). Introduction: VSD closure using conventional pmVSD occluders has been largely abandoned because of an unacceptable high rate of complete heart block (CHB). The advantages of Duct Occluders and VSD Coil are supposed to reduce the drawbacks of previous devices, especially CHB complications. Method: Patients underwent percutaneous pmVSD closure were divided into Coil group (using VSD Coil, n  = 71) and DO group (using Duct Occluders, n  = 315). Patient demographics, clinical presentations, echocardiography measurements, procedure details and follow‐up data were collected. Result: The procedure success rate was high in both DO group (95.6%) and Coil group (97.2%, P  = .53). The closure rate immediately after procedure in the DO group was higher than that in the Coil group (76.8% vs. 58.0%, P  < .01). After 6 months, the closure rate was not significantly different between the 2 groups (DO group 91.3% vs. Coil group 84.1%, P  = .07). The mean follow‐up time was 61.4 ± 24.1 months. The major complication rate was low in both groups (DO group 1.9% vs. Coil group 1.4%, P  = .78). Two patients (0.7%) in the DO group and one patient (1.4%) in the Coil group with CHB needed permanent pacemaker ( P  = .5). Device embolization (3 patients, 1.0%) and endocarditis (1 patient, 0.3%) occurred only in the DO group. There was no death, disability or other major complications detected in either group. Conclusion: Percutaneous pmVSD closure using either Nit‐Occlud Lê VSD Coil or Duct Occluders is feasible, safe and efficacious in selected patients. The main problems of Duct Occluders are unsuitable defect anatomy and device embolization while VSD Coil disadvantages are residual shunt and hemolysis.